Long-Term Variability and Trends in the Caribbean Sea. (17th February 2011) - Jury, Mark R.
Abstract : Upper ocean conditions in the Caribbean Sea are studied for long-term variability and trends using filtered surface observations and ocean model reanalysis fields. A principal component analysis is made, and trends in the leading mode are extracted. Sea surface temperature shows an accelerating upward trend while air pressure exhibits quasidecadal fluctuations. Sea surface height and subsurface temperature rise linearly while subsurface salinity exhibits fresher upper and saltier lower layers. The amplitude of warming is highest in the southern Caribbean east of 75°W near 150 m and lowest near the surface, indicating little role for a top-down process such as air-sea exchange. The freshening surface layer does not appear connected to river discharge or regional rainfall, so changes in ocean advection and sources are the likely drivers. Westward currents exhibit a reduction of throughflow and an influx from the Windward Passage. The Caribbean Current has slowed ~0.06 m/s in the reanalysis era. Crop yields show little sensitivity to ocean conditions but tend to follow rainfall. Marine catch per capita in the Caribbean follows subsurface currents and vertical motion but is less affected by temperature and salinity.